A Praise of Falsehood: the Whirlpool of Imaginary Sounds - Cornia, Nicholas 1989-; Dialogues Artistic Research Enhancing Rome, Italy 14/05/2025; Conservatorio Santa Cecilia (Rome, Italy) (Via dei Greci, 18 – 00187 – Roma Conservatorio Statale di Musica di Roma “Santa Cecilia”, 2025)
Despite recent cultural changes, the Early Music movement remains mostly a bastion of "truth" and "authenticity" in modern times' turbulent sea of doubt. Conversely, the whirlpool of artifice project wishes to legitimize a place for falsification, fiction and imagination in the realm of historically informed practice. The hermetic title A Whirlpool of Imaginary Sounds embeds in itself the main premises of the project. First, it alludes to Italian philosopher Giulio Camillo (1480-1544), who proposed a device called artificiosa routa, a generative model ante litteram to systematize the creative process of poets and orators. Analogously with Camillo and many transgressive thinkers of the 16th and early 17th century, the project wishes to investigate the plurality of worlds hidden behind the (re)combinations of a musical knowledge system. Secondly, it is an homage to writers of fiction and thinkers like Jorge Luis Borges and Umberto Eco. Mythical creatures as well as utopian lands share a similar ascendant on our minds: through placing themselves outside reality they become powerful emblems revealing the inner meaning of things. Inspired by proto-scientific thought, poetry, devices of wonder and games from the 16th and early 17th centuries the Whirlpool of Imaginary Sounds aims to reconsider our past through polyphonic music that never was. In this project, I aspire to discover the liminal space between corpus-based musicking, forgery and period composition by reshaping the role of knowledge, either actual or imaginary, and its systematization.
FRIS
0
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research